Quantitative and Qualitative Analysis of Differences in Work-Related Injury Incidence in Construction: A Comparative Study between the Guayas and Pichincha Provinces in Ecuador, 2014-2023 - Gómez García, Antonio Ramón (2025)
Workplace injuries remain a significant issue in the construction sector in Ecuador, particularly in provinces with high urban development and workforce populations. This study aims to identify the factors contributing to differences in accident incidence between Guayas and Pichincha. Using administrative data from 2014 to 2023, age-standardized incidence rates (ASIR) and incidence rate ratios (IRR) were calculated. Additionally, a questionnaire was designed and administered to explore differences among experts (Mann-Whitney U test and Cohen’s Kappa index). The analysis revealed that Guayas consistently had higher ASIRs and twice the IRR compared to Pichincha. Experts from Guayas highlighted macro-level factors as primary, whereas those from Pichincha emphasized micro-level factors, with no significant differences at the meso level. These differences may be attributed to uneven enforcement of regulations and cultural attitudes toward safety. It is recommended to enhance labor inspections in Guayas and conduct nationwide research for a deeper understanding.